A Study of Nuclear Properties of 112-Xe Even-Even Isotopes By The Interacting Boson Model-1 (IBM-1) - Kazem Jabar, Ibraheem; Abd Al-Ammeer Al-Sharefi, Mohammad (Al-Qadisiyah Journal of Pure Science, 2018)
In this search, 112-Xe isotope has been studies by the interacting boson model (IBM- 1) to determine the energy levels and the electric quadruple moments Q21+ , In addition, by the program IBMT was used for evaluating the reduced transition probability B(E2). The square of rotational energy and the moment of inertia were calculated . spin and parity for some energy levels, which were never determined experimentally . It was found that the of (3.293 , 2.338 , 2.069, 1.617 , 1.25, 0.658 )MeV for112Xe spin and parity of are (122+,102+,82+,62+,42+,22+,02+), respectively. According to the IBM, It was found that the 112-Xe isotope the belong to the transition region SU(5)â†’O(6. )